University physics - Young, Hugh D.; Freedman, Roger A.;Sadin, T. R.;Lewis Ford, A. (Reading, Massachusetts : Addision-Wesley Publishing Company, 1996)
An introduction to the elements comprising an introductory physics course. The emphasis in this text is on the physicist's approach to understanding nature and the importance of model building to set up the correct analysis of the problems. This edition includes material based on latest research.
Chapter 1. Units, Physical Quantities and Vectors -- Chapter 2. Motion along a Straight line -- Chapter 3. Motion in Two or Three Dimension -- Chapter 4. Newton's Law of Motion -- Chapter 5. Applications of Newton's Laws -- Chapter 6. Work and Kinetic Energy -- Chapter 7. Potential Energy and Energy Conservation -- Chapter 8. Momentum, Impulse and Collisions -- Chapter 9. Rotation of Rigid Bodies -- Chapter 10. Dynamics of Rotational Motion -- Chapter 11. Equilibrium and Elasticity -- Chapter 12. Gravitation -- Chapter 13. Periodic Motion -- Chapter 14. Fluid Mechanics -- Chapter 15. Temperature and Heat -- Chapter 16. Thermal Properties of Matter -- Chapter 17. The First Law of Thermodynamics -- Chapter 18. The Second Law of Thermodynamics -- Chapter 19. Mechanical Waves -- Chapter 20. Wave Interference and Normal Modes -- Chapter 21. Sound and Hearing -- Chapter 22. Electric Charge and Electric Field -- Chapter 23. Gauss's Law -- Chapter 24. Electric Potential -- Chapter 25. Capacitance and Dialectics -- Chapter 26. Current, Resistance and Electromotive Force -- Chapter 27. Direct-Current Circuits -- Chapter 28. Magnetic Field and Magnetic Forces -- Chapter 29. Sources of Magnetic Field -- Chapter 30. Electromagnetic Induction -- Chapter 31. Inductance -- Chapter 32. Alternating Current -- Chapter 33. Electromagnetic Waves -- Chapter 34. The Nature and Propagation of Light -- Chapter 35. Geometric Optics -- Chapter 36. Optical Instruments -- Chapter 37. Interference -- Chapter 38. Diffraction -- Chapter 39. Relativity -- Chapter 40. Protons, Electrons and Atoms -- Chapter 41. The Wave Nature of Particle -- Chapter 42. Quantum Mechanics -- Chapter 43. Atomic Structure -- Chapter 44. Molecules and Condensed Matter -- Chapter 45. Nuclear Physics -- Chapter 46. Particle Physics and Cosmology.
Includes index.
Keywords: PHYSICS